Affiliation, Loyalty, and Sustainability in Virtual Community: a Case Study of Facebook - Chen, Chia Chen (2006)
Within the popularity of the concept Web2. Facebook.com has become one of the most popular online social networking sites in the world. The knowledge-sharing action is the major activity in the virtual community (VC). The aim of this dissertation is to identify the relationship between knowledge-sharing activity and other variables such as community participation, community promotion, and the concept of trust in the VC. Furthermore, the latter three variables also link to the factor of member's loyalty toward the virtual community provider. The research structure is divided into two stages in order to define the correlation between each variable. The final part of this study includes the discussion of the finding from the survey related to Facebook, and it has been concluded that knowledge-sharing activity related to the community participation in the Stage 1, and the community participation and community promotion are related the member's loyalty toward the virtual community provider. The member's loyalty is the key for the virtual community to maintain the sustainability. Hence, in order to provide the sustainability, the VC provider needs to pay attention to knowledge-sharing activity.